2018
DOI: 10.1002/cplu.201700550
|View full text |Cite
|
Sign up to set email alerts
|

Macrocycles Bearing Ferrocenyl Pendants and their Electrochemical Properties upon Binding to Divalent Transition Metal Cations

Abstract: Metal complexes of Cu2+, Co2+, Cd2+, Zn2+, and Ni2+ formed with the ligands [Fc(cyclen)] (1) and [Fc(cyclen)2] (2) (Fc=ferrocene, cyclen=1,4,7,10‐tetraazacyclododecane) are synthesised and characterised. The X‐ray structure of the Cu2+ complex of 2, Fc([Cu(cyclen)(CH3CN)]2(ClO4)4, is reported, and shows that the two positively charged Cu2+‐cyclen units have a coordination number of five, adopting a distorted trigonal‐bipyramidal configuration. The Cu2+‐cyclen units are arranged in a trans‐like configuration wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The interaction between Fc and amines has been the subject of extensive research due to its potential wide application range, including the design of metal ion receptors and sensors [8][9][10]63,[68][69][70][71][72]. However, despite numerous studies, the details of this interaction and the oxidation mechanism of ferrocene-bearing amine compounds have remained elusive until recently, where the oxidation mechanism of N,N-dimethylaminomethylferrocene (20, Fc-CH 2 -N(CH 3 ) 2 ), which can be considered as the parent ligand for many Fc receptors presented in this review, was evaluated and the oxidation product identified (Scheme 2) [7].…”
Section: Ferrocene-based Electrochemical Sensors Using Nitrogen-conta...mentioning
confidence: 99%
“…The interaction between Fc and amines has been the subject of extensive research due to its potential wide application range, including the design of metal ion receptors and sensors [8][9][10]63,[68][69][70][71][72]. However, despite numerous studies, the details of this interaction and the oxidation mechanism of ferrocene-bearing amine compounds have remained elusive until recently, where the oxidation mechanism of N,N-dimethylaminomethylferrocene (20, Fc-CH 2 -N(CH 3 ) 2 ), which can be considered as the parent ligand for many Fc receptors presented in this review, was evaluated and the oxidation product identified (Scheme 2) [7].…”
Section: Ferrocene-based Electrochemical Sensors Using Nitrogen-conta...mentioning
confidence: 99%
“…In some cases, a metal–iron interaction, e.g., as shown in complex IV [79], could be observed depending on the ring size of the ferrocenophane ligand [8285]. Furthermore, ferrocenophanes functionalized with bridges containing various heteroatoms were utilized as ion sensors for a wide variety of applications [8690]. An example (complex V ) with an additional diyne moiety is given in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[82][83][84][85] Furthermore, ferrocenophanes functionalized with bridges containing various heteroatoms were utilized as ion sensors for a wide variety of applications. [86][87][88][89][90] An example (complex V) with an additional diyne moiety is given in Figure 2 To the best of our best knowledge, no ferrocenophanes formed via RCAM have been reported to date. With this contribution, we would like to present the first RCAM of 1,1'-diacetylenic ferrocenes 1 (a: n =2; b: n = 3) to form the corresponding alkynebridged ferrocenophanes 2 (a: n =2; b: n = 3; Figure 2).…”
mentioning
confidence: 99%